2023
DOI: 10.15252/embj.2022112699
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome biogenesis factors—from names to functions

Abstract: The assembly of ribosomal subunits is a highly orchestrated process that involves a huge cohort of accessory factors. Most eukaryotic ribosome biogenesis factors were first identified by genetic screens and proteomic approaches of pre‐ribosomal particles in Saccharomyces cerevisiae. Later, research on human ribosome synthesis not only demonstrated that the requirement for many of these factors is conserved in evolution, but also revealed the involvement of additional players, reflecting a more complex assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 483 publications
2
80
0
Order By: Relevance
“…One could hypothesize that a HIF-dependent gene, such as a splicing factor, is directly or indirectly responsible for repressing the processing of RPS24S. Moreover, since many proteins of the small ribosomal subunit are involved in ribosome biogenesis (37), perhaps RPS24S is the favored isoform for this process and is repressed in hypoxia through energy stress-induced mTORC1 repression. Interestingly, even though mTORC1 inhibition induces autophagy, RPS24S repression through mTORC1 inhibition was not reversed upon the addition of Bafilomycin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One could hypothesize that a HIF-dependent gene, such as a splicing factor, is directly or indirectly responsible for repressing the processing of RPS24S. Moreover, since many proteins of the small ribosomal subunit are involved in ribosome biogenesis (37), perhaps RPS24S is the favored isoform for this process and is repressed in hypoxia through energy stress-induced mTORC1 repression. Interestingly, even though mTORC1 inhibition induces autophagy, RPS24S repression through mTORC1 inhibition was not reversed upon the addition of Bafilomycin (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NOC1 in yeast works as a heterodimer with NOC2 during the initial transport and maturation of the ribosomal RNA (rRNA), a process that is completed by NOC2/NOC3 heterodimers (Milkereit et al, 2001). Furthermore, studies on the distribution of affinity-tagged NOC1 and, more recently, proteomics and crosslinking coupled to mass spectrometry confirmed the presence of NOC1 in the early pre-60S complex (Sailer et al, 2022;Dorner et al, 2023), while cryo-EM studies showed its role in the formation of heterodimers with NOC2, essential for the quality-control checkpoint of the maturation of the large ribosome subunit (Sanghai et al, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…NOC1 is a nucleolar protein that, together with NOC2 and NOC3, plays a critical role in the maturation of rRNA and the transport of the pre-ribosomal subunits (Sailer et al, 2022;Dorner et al, 2023). NOC1 in yeast works as a heterodimer with NOC2 during the initial transport and maturation of the ribosomal RNA (rRNA), a process that is completed by NOC2/NOC3 heterodimers (Milkereit et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Construction of this mega‐Dalton complex of rRNAs and ribosomal proteins is intricately coordinated by numerous additional factors. Recent advances and a comparison of ribosome assembly pathways across species will be highlighted in the review article on ribosome biogenesis factors by Ulrike Kutay and colleagues (Dörner et al , 2023).…”
mentioning
confidence: 99%